ANALYSIS OF FACTORS INFLUENCING THE UNEMPLOYMENT RATE ON POVERTY RATE IN INDONESIA - Fitri Indri Wahyuni; Syalsa, Syalsa Billa Aulia Hakim; Wanda, Wanda Lestari; Azhari, M. Azhari Ramadhan; Fahri, Fahri Reza (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Poverty is a multifaceted problem related to low incomes, illiteracy and poor health, gender inequality and precarious living conditions. Getting out of poverty cannot happen automatically Apart from the problems of unemployment, education, health and others which are clearly closely related to the problem of poverty. Poverty is one of the problems faced by developing countries, including Indonesia. In Indonesia, poverty is a problem The problem of unresolved poverty varies between provinces in Indonesia, but the focus is on the people. The poverty rate in Java is very high compared to other provinces in front of the island of Java. Even though each region has accessibility and facilities to meet the needs of life. Especially the province of Java Where it is easy to get to government centers and vice versa Regions from the center to Java compared to areas outside Java Java Island This study looks at GDP, education (literacy), unemployment (TPT), poor life expectancy in Java Island 2005-2011.